Adequate Antenatal Care Visits among Tribal Women in Bangladesh - Rezaul Karim, A.N.M. (Journal of Techno-Social, 2020)
Maternal mortality is a global concern, and peaks in developing countries. Adequate antenatal care services (ANCs) are indispensable for both maternal and fetal survival. A global trend leads us to the notion that aboriginal women are somewhat less privileged than non-tribal mothers around the world. Hence, this study determines the association of socio-economic status and adequate use of ANC facilities by Bangladesh's tribal women. This study is a quantitative study using a convenient sampling technique. Semi-structured questionnaires were used to obtain data on married women (n=556) between the ages of 15–49 who had children aged 1 year or under. The data were analyzed using the SPSS program (version 20). Associations were determined using Chi-square test and regression analysis of maternal health care services and the adequacy of ANC use. Significance was determined at p-value